Evaluation of the Antimicrobial Activity of Phytochemicals from Tea and Agarwood Leaf Extracts against Isolated Bacteria from Poultry and Curd - Shah Rucksana Akhter Urme; Syeda Fahmida Ahmed; Mohammed Mostafa Al Quadir; Mst Rubaiat Nazneen Akhand; Mohammad Mehedi Hasan Khan (The Scientific World Journal)
Antibiotic-resistant bacteria are becoming increasingly common, leading to a global health crisis. The effects of abusing antibiotics not only increase pathogenic resistance but also cause various diseases and syndromes. Gut microbiota contains many beneficial roles for health, while antibiotics kill both pathogens and gut microbiota which is considered one of the major side effects of antibiotics. In fact, new antibiotic compounds are needed in this urgent scenario; phytoremediation is the oldest but most effective method, and research on the antibacterial properties of several types of medicinal plants has already been conducted. Tea and agarwood plants are well known for their economic contribution in both beverage and cosmetic production, as well as for their medicinal value. In this study, tea and agarwood leaf extracts were analyzed for their antimicrobial activity against both pathogenic and beneficial bacteria. Fresh tea (Camellia sinensis) leaves were collected in three varieties, namely, BT-6 from Sylhet, BT-7 from Moulvibazar, and BT-8 from Habiganj; also, green tea (nonfermented tea), black tea (fully fermented tea), and agarwood (Aquilaria malaccensis) were collected from Sylhet region of Bangladesh. Unlike commercial antibiotics, which have side effects on probiotics (beneficiary bacteria), leaf extract activities were analyzed to check if they had positive effects on probiotics that can be found in the gastrointestinal tract as well as dairy products. Potential beneficiary bacteria, Lysinibacillus macroides strain SRU-001 (NCBI accession no. MW665108), and pathogenic bacteria, Aeromonas caviae strain YPLS-62 (NCBI accession no. MW666783), were isolated from the small intestine of poultry and curd, respectively. Tea and agarwood leaves (5 g powder/80 mL methanol) with solvents were kept for seven days at room temperature, and extracts were applied for antimicrobial assays by the disc diffusion assay against the isolated bacteria. 50 µL of each leaf extract was examined against 50 µL of each bacterial culture, where gentamicin was a control. After 24 hours of incubation, tea and agarwood leaf extracts showed an 11–15 mm zone of inhibition against pathogenic A. caviae, while only BT-8 showed 7 mm (disc diameter 6 mm) against probiotic L. macroides. However, compared to leaf extracts, gentamicin showed a 27 mm zone of inhibition against both L. macroides strain SRU-001 and A. caviae strain YPLS-62 bacteria. This research clearly indicates that gentamicin kills both pathogenic and beneficiary bacteria, while leaf extracts from tea and agarwood plants contain antimicrobial activity against only pathogenic A. caviae but no effects on probiotic L. macroides. This outcome indicates not only the potential therapeutic values of tea and agarwood leaves as antibiotics over commercial antibiotics but also the chance of having pathogens in curd and potential beneficial bacteria from the poultry small intestine.